2015
DOI: 10.1097/iae.0000000000000847
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Foveal Avascular Zone Size With Foveal Morphology in Normal Eyes Using Optical Coherence Tomography Angiography

Abstract: Optical coherence tomography angiography provides a noninvasive method to visualize and measure the superficial and deep plexus FAZ in a normal population. The FAZ can vary in size and shape, with the FAZ area significantly larger in the deep compared with the superficial plexus. Both superficial and deep FAZ area correlate inversely with foveal thickness and volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
236
10
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(296 citation statements)
references
References 33 publications
41
236
10
9
Order By: Relevance
“…On the other hand, vascular disruption in eyes suffering from DR can be so pronounced that in two eyes deep FAZ was not completely contained in the 3 3 3-mm scan. This could be explained considering that FAZ is usually larger at deep capillary plexus, and, as already mentioned, deep vascular layer disruption is more pronounced in DR. 17,28 With regard to vessel density, our study showed a poor interchangeability across different angiocubes for every plexus and every subgroup. Several aspects should be considered to interpret this finding.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…On the other hand, vascular disruption in eyes suffering from DR can be so pronounced that in two eyes deep FAZ was not completely contained in the 3 3 3-mm scan. This could be explained considering that FAZ is usually larger at deep capillary plexus, and, as already mentioned, deep vascular layer disruption is more pronounced in DR. 17,28 With regard to vessel density, our study showed a poor interchangeability across different angiocubes for every plexus and every subgroup. Several aspects should be considered to interpret this finding.…”
Section: Discussionmentioning
confidence: 71%
“…The FAZ area was manually measured at all retina, superficial, and deep vascular layers using a previously published method. 16,17 Briefly, the FAZ area was encircled using the polygon selection tool and its area was recorded in squared millimeters.…”
Section: Quantitative Analysis Of Oct-a Imagesmentioning
confidence: 99%
“…15,50,51 Studies assessing FAZ measurement using OCTA technology have recently been published. 12,13,24,31,45,46,52,53 These studies reported the FAZ area of normal eyes to be 0.250 to 0.474 mm 2 , depending on the characteristics of the study participants, type of OCTA machine, segmentation, and image analysis method. In patients with glaucoma, the FAZ area is reported to be enlarged compared with that in normal controls, which ranged from 0.360 to 0.435 mm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of FAZ area and the evaluation of FAZ integrity are very important because the enlargement of FAZ precedes the occurrence of microaneurisms and the diabetic retinopathy in this stage can be reversed [24,25]. Ischemic maculopathy is an ophthalmoscopically occult maculopathy if there is no associated with cotton wool spots.…”
Section: Editorialmentioning
confidence: 99%